1990
DOI: 10.1143/jjap.29.138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Temperature and V/III Ratio on MOCVD-Grown GaAs-on-Si

Abstract: Effects of growth temperature and V/III ratio on surface morphology, crystallinity and residual impurities of MOCVD-grown GaAs-on-Si have been studied. The effects are different from those on MOCVD-grown GaAs-on-GaAs. The difference arises from the heteroepitaxial problems. High silicon concentrations are found in all the GaAs-on-Si, and the electrical activation of silicon as a donor reaches 100% for higher growth temperatures. Crystallinity improves but surface morphology degrades with increasing growth temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Among them, the three-step growth method [16,17] and the dislocation filter layer (DFL) with multilayer quantum dots (QDs) [18][19][20] have obtained commendable experiment results. The threestep growth method is a modified two-step growth method by inserting an intermediate-temperature (IT) layer between the low-temperature (LT) layer and the hightemperature (HT) layer.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the three-step growth method [16,17] and the dislocation filter layer (DFL) with multilayer quantum dots (QDs) [18][19][20] have obtained commendable experiment results. The threestep growth method is a modified two-step growth method by inserting an intermediate-temperature (IT) layer between the low-temperature (LT) layer and the hightemperature (HT) layer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a three-step growth, the modified two-step growth method in which an intermediate-temperature (IT) layer is added between LT and HT layer, was commonly employed in recent years [128,[141][142][143]. Nozaki et al [144] proposed and reported that the three-step growth method in GaAs-on-Si improved the surface morphology, as well as crystallinity. The detailed mechanism of this improvement was not clearly understood, but it was ascribed to the GaAs top layer grown at HT without direct contact to the LT nucleation layer.…”
Section: Nucleation and Iii-v Buffer Layermentioning
confidence: 99%
“…In general, the dislocation density in AlGaAs grown on Si substrate increases with the Al content, and the quantum efficiency of AlGaAs solar cell on Si decreases. Many efforts [14][15][16][17][18][19] have been done to improve the crystal quality of GaAs and AlGaAs on GaAs, for many years. InGaP is also being investigated [20] as a material for top cell instead of AlGaAs.…”
Section: Other Activitiesmentioning
confidence: 99%